Immediate load in single-tooth restorations: a clinical prospective study - Porras, Andrés Felipe; Arismendi-E., Jorge Alberto; Arango-B., Paola Andrea (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: immediate loading of implants has become a viable treatment alternative that offers multiple benefits for patients such as providing immediate function and esthetics, reduction of surgical trauma and less treatment time. A controlled prospective clinical trial was conducted to evaluate the success of immediately loaded implants for single-tooth restoration following consensus protocols in recent literature. Methods: twenty-one 3.75 x 13mm RBM-treated surface internal connection implants (Renova®, Lifecore Biomedical Inc., Chaska Mn.) were placed in 17 systemically healthy patients (6 males, 11 females), ages between 18 and 74 years who required single-tooth replacement in the anterior and premolar regions of both jaws. Results: the 18-month cumulative success rate for this study was 95.2%. According to the statistical analysis in this study, immediate loading of implants for single-tooth restoration compares favorably to the two-stage protocol and a direct correlation between the distance from bone to contact point and papilla filling was found. Conclusions: results from the present study indicate that the single-tooth restoration in the anterior area with immediately loaded surface-treated threaded titanium implants and no occlusal function is a viable treatment alternative with a success rate greater than 95%, comparable to the conventional loading protocol.